Pertanian Ramah Lingkungan di Daerah Tangkapan Air Danau Rawapening - Neny Hidayati; Tri Retnaningsih Soeprobowati (Universitas Sebelas Maret, 2017)
The green revolution that marked a major shift in agricultural technology to meet the world's food needs brought the excessive use of inorganic fertilizers. Phosphorus and nitrogen in the fertilizer run through the lake causes eutrophication. As a result, an uncontrolled population of aquatic plants emerges which in turn, reduce the lake function. To overcome eutrophication problem, sustainable and environmentally friendly agriculture is expected to control the supply of nutrients into the lake. Therefore, in GERMADAN (Gerakan Penyelamatan Danau/Save Indonesian Lake Movement) Rawapening, sustainable agriculture became one of the superpriority programs. The purpose of this study is to assess the implementation of sustainable agriculture specifically on the use of inorganic fertilizer. Secondary data was collected and interview with agricultural practitioners was done to gather primary data. The result showed that the highest dosage of fertilizer was in Ambarawa and Bandungan districts. It is necessary to prioritize the development of environmentally friendly agriculture in those area. To reduce the use of inorganic fertilizer, efforts should be made by the Government in facilitating the production of affordable organic fertilizer.